Dietary inclusion of neem leaf powder on growth performance, blood biochemical parameters and profitability of broilers (Bangladesh Journal of Animal Science, 2022)
The experiment was carried out to investigate the effects of neem (Azadirachta indica) leaf powder (NLP) over a period of 35 days on the growth performance, dressing parameters, serum biochemical parameters and profitability of broiler meat. Day old broiler chicks (n = 320) were randomly assigned to five dietary groups, each with four replicates. The dietary treatment groups were; control (basal diet; no additives), antibiotic (basal diet + antibiotic), NLP 0.25% (basal diet + 0.25% NLP), NLP 0.375% (basal diet + 0.375% NLP) and NLP 0.50% (basal diet + 0.50% NLP). Results showed that the body weight, body weight gain, feed intake and FCR were differed significantly (P0.05). Better (P0.05) different among the dietary groups. Serum glucose, triglyceride, GOT, GPT and cholesterol level were non-significant (P>0.05) among the dietary groups. However, HDL was significantly (P